2007
DOI: 10.1017/s0265021506001323
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol vs. ondansetron for the prevention of postoperative nausea and vomiting following gynaecological surgery

Abstract: The prophylactic administration of 1 mg intravenous haloperidol or 4 mg ondansetron, in female patients undergoing gynaecological surgery, did not improve the overall incidence of nausea and/or vomiting vs. placebo. However, haloperidol 1 mg proved to be an effective antiemetic in the early observation period without significant adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…In a more recent study, haloperidol 1 mg iv proved to be an effective antiemetic for the early (0-2 hr) prevention of nausea and vomiting. 15 Yet, the overall 24 hr incidence of PONV (41%) did not improve compared with placebo (56% incidence ). In these studies, study medications were administered at the start of anesthesia.…”
Section: Discussionmentioning
confidence: 88%
“…In a more recent study, haloperidol 1 mg iv proved to be an effective antiemetic for the early (0-2 hr) prevention of nausea and vomiting. 15 Yet, the overall 24 hr incidence of PONV (41%) did not improve compared with placebo (56% incidence ). In these studies, study medications were administered at the start of anesthesia.…”
Section: Discussionmentioning
confidence: 88%
“…They concluded that the FDA recommendations for additional 12 lead ECG monitoring after administration of low dose droperidol are unwarranted. Recently, Aouad et al 5 observed that the mean QTc interval was not significantly different after intravenous haloperidol compared to ondansetron and saline. Therefore, we did not perform 12 lead ECGs to evaluate the QT interval.…”
Section: Discussionmentioning
confidence: 98%
“…Prophylactic administration of haloperidol 1 mg proved to be an effective antiemetic for the early (0-2 hr) prevention of nausea and vomiting following gynecological surgery. 5 Yet, the overall 24 hr incidence of PONV (41%) did not improve compared to placebo (56%). In these studies, haloperidol was administered at the start of anesthesia.…”
Section: Conclusion : Le Moment Choisi Pour L'administration De 2 Mg mentioning
confidence: 88%
See 2 more Smart Citations